2019
DOI: 10.5194/acp-19-2283-2019
|View full text |Cite
|
Sign up to set email alerts
|

Primary emissions versus secondary formation of fine particulate matter in the most polluted city (Shijiazhuang) in North China

Abstract: Abstract. Particulate matter (PM) pollution is a severe environmental problem in the Beijing–Tianjin–Hebei (BTH) region in North China. PM studies have been conducted extensively in Beijing, but the chemical composition, sources, and atmospheric processes of PM are still relatively less known in nearby Tianjin and Hebei. In this study, fine PM in urban Shijiazhuang (the capital of Hebei Province) was characterized using an Aerodyne quadrupole aerosol chemical speciation monitor (Q-ACSM) from 11 January to 18 F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 60 publications
9
81
0
Order By: Relevance
“…For example, emission rates from meat charbroiling are around 15 g kg −1 , three orders of magnitudes greater than those obtained here or reported for domestic cooking. The significantly higher emissions from commercial kitchens compared to domestic kitchens are also observed in the case of China, where COA is a prominent fraction of the aerosol in urban environments . This hypothesis is consistent with the observation of COA downwind of restaurants and during mobile measurements in restaurant areas .…”
Section: Resultssupporting
confidence: 84%
“…For example, emission rates from meat charbroiling are around 15 g kg −1 , three orders of magnitudes greater than those obtained here or reported for domestic cooking. The significantly higher emissions from commercial kitchens compared to domestic kitchens are also observed in the case of China, where COA is a prominent fraction of the aerosol in urban environments . This hypothesis is consistent with the observation of COA downwind of restaurants and during mobile measurements in restaurant areas .…”
Section: Resultssupporting
confidence: 84%
“…COA is an important POA in urban environments worldwide (Figure ). The megacities in China and India showed much higher COA concentrations (4.8 ± 3.3 μg/m 3 ) than those in North America (1.4 ± 0.50 μg/m 3 ) and Europe (1.1 ± 0.50 μg/m 3 ), and the highest COA concentrations were observed in two most polluted cities, that is, Shijiazhuang, China (14.2 μg/m 3 ; Huang et al, ) and Kanpur, India (9 μg/m 3 ; Thamban et al, ). Although the COA concentrations varied spatially, the contributions to OA were relatively similar, which were 17.4 ± 5.6%, 20.2 ± 5.9%, and 15.4 ± 5.0% in Asia, North America, and Europe, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…However, recent measurements of OH radicals at a suburban site in Beijing reported wintertime OH radical concentrations at noontime ranged from 2.4 × 10 6 cm −3 during severe pollution events (k OH ∼ 27 s −1 ) to 3.6 × 10 6 cm −3 during relatively clean events (k OH ∼ 5 s −1 ) (Tan et al, 2018). These OH radical concentrations are nearly an order of magnitude larger than those predicted by global models for northern China in winter (Lelieveld et al, 2016). The higher-thanexpected OH concentrations and moderate OH reactivity in Beijing resulted in fast photochemistry in winter (Lu et al, 2019), explaining the high contribution of secondary aerosol during wintertime severe haze events (Huang et al, 2014).…”
Section: Daytime Evolution Of Secondary Species In Summer and Wintermentioning
confidence: 88%
“…Compared to primary aerosol that is relatively well constrained in terms of the emission sources, secondary aerosol is still not well understood, likely due to its variable precursors, complex formation and atmospheric transformation processes mediated by meteorological conditions Petäjä et al, 2016;Tie et al, 2017;Xu et al, 2017). A number of studies have investigated the formation and aging processes of secondary aerosol (Takegawa et al, 2009;Huang et al, 2014Huang et al, , 2019Sun et al, 2014Sun et al, , 2016Wang et al, 2016;Duan et al, 2019). For example, field measurements showed that aqueous-phase oxidation of SO 2 could be an important formation pathway of sulfate at high RH during haze events Elser et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation